Gender-based violence: prevalence, sexist imaginaries, and myths among university students - Trujillo Cristoffanini, Macarena (2020)
The aim of this study is to identify aspects related to gender-based violence at Chilean universities, with a focus on three areas of analysis: the prevalence of violence against women in heterosexual relationships; the persistence of traditional gender constructs; and the reproduction of myths about this form of abuse, as well as the sexist imaginaries present in the student’s experiences. Theoretical support is drawn from feminist analyses that have examined the power structures in which these aggressions survive and reproduce, as well as the social dynamics that naturalize them. Studies have found that higher education is neither a protective factor against violence nor a tool that dismantles the gender imaginary that supports it. At a methodological level, 1,120 surveys were administered at three Chilean universities, encompassing the three aforementioned areas of analysis. The results point to the continuing prevalence of violence against women, as well as the endurance of myths and sexist imaginary that invisibilize the reproduction of gender power relations. The discussion and conclusions highlight the role of education and higher education institutions in driving changes in this area.